2022
DOI: 10.3389/fphar.2022.886337
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Growth Sites on the Phenolic Contents and Antioxidant Activities of Three Algerian Mentha Species (M. pulegium L., M. rotundifolia (L.) Huds., and M. spicata L.)

Abstract: Research studies about the effect of environmental agents on the accumulation of phenolic compounds in medicinal plants are required to establish a set of optimal growth conditions. Hence, in this work, we considered the impact of habitat types, soil composition, climatic factors, and altitude on the content of phenolics in Mentha species [M. pulegium L. (MP), M. rotundifolia (L.) Huds. (MR), and M. spicata L. (MS)] grown in different regions of Algeria. The phenolic contents and antioxidant activities were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 57 publications
4
11
1
Order By: Relevance
“…Thus, the total bioactive compounds expression pattern study revealed that B. lacera is a rich source of total bioactive compounds, and it contains a higher amount of total flavonoids than total phenolics. Genotypic specificity is among the various factors that govern the variability of total phenolics and total flavonoids contents in plants [34,35] . The higher total flavonoid content found in this species is consistent with previous findings that reported that B. lacera contains more total flavonoids than total phenolics [36,37] .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, the total bioactive compounds expression pattern study revealed that B. lacera is a rich source of total bioactive compounds, and it contains a higher amount of total flavonoids than total phenolics. Genotypic specificity is among the various factors that govern the variability of total phenolics and total flavonoids contents in plants [34,35] . The higher total flavonoid content found in this species is consistent with previous findings that reported that B. lacera contains more total flavonoids than total phenolics [36,37] .…”
Section: Resultssupporting
confidence: 91%
“…Genotypic specificity is among the various factors that govern the variability of total phenolics and total flavonoids contents in plants. [34,35] The higher total flavonoid content found in this species is consistent with previous findings that reported that B. lacera contains more total flavonoids than total phenolics. [36,37] Moreover, several other species of the Blumea genus, such as Blumea lacineta, [38] Blumea eriantha, [39] and Blumea balsamifera, [40] contain higher concentrations of total flavonoids than total phenolics.…”
Section: B Lacera Phytochemical Profiles Total Phenolics and Flavonoi...supporting
confidence: 91%
“…[ 43 , 49 , 50 ]. The biotic (pathogens and herbivores) and abiotic factors (climatic conditions, soil composition, altitude, drought stress, salinity) [ 48 , 51 , 52 ] could also be implicated. Indeed, Navarro et al [ 48 ] and Shahbazi et al [ 7 ] reported that water stress enhances the production of oxygen species and free radicals in plants, which increased biosynthesis and the accumulation of phenolic compounds as a plant protection mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, UV radiation unbalances the plant redox status, and the plant is consequently forced to overexpress some secondary metabolites more than others to counteract the strong oxidative stress [ 50 , 52 ]. A recent study investigated the impact of growth sites on the phenolic contents and antioxidant activities of three Algerian species of Mentha [ 23 ]. Analyzing different M. pulegium ecotypes, the authors observed that plant growth in the sampling site characterized by mild summer and hot winter, situated at the lowest altitude, and with medium-type soil with a balanced texture (moderate humidity and non-saline) had the highest content of polyphenols and, consequently, showed the best antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that pedoclimatic conditions can also influence the morphoanatomical and polyphenolic profile of plants and, consequently, the biological activity of their extracts [ 22 , 23 ]. However, only a few studies have been conducted to date on M. pulegium in this regard.…”
Section: Introductionmentioning
confidence: 99%